Dune gardening? A critical view of the contemporary coastal dune management paradigm. Issue 2 (2nd February 2021) - Cooper, Andrew; Jackson, Derek
Abstract : Modern coastal dune management is viewed largely through the prism of dune ecology. Achieving maximum biodiversity and preserving priority species are the primary objectives and management is based on interventions (grazing, mowing, burning, reseeding, and artificial destabilisation) to achieve that purpose. Under non‐managed conditions, dune vegetation tends to evolve temporally following well‐established succession patterns that lead to a low diversity scrub or woodland. Achieving high diversity involves resisting succession so as to preserve the more biodiverse, earlier stages. The net effect of management is to create dunes with a network of vegetation types that conform to human wish lists. Rather than natural environments, such interventions reduce dunes to the status of parklands. The natural status of NW European dunes under the conditions of relatively stable sea level and generally limited sand supply over the past few thousand years, and certainly since the Little Ice Age (1650–1800), is to be at a relatively well‐vegetated and advanced stage of succession. Modern dune management effectively amounts to a form of "dune gardening" to maintain a status that is not natural (i.e., attuned to the ambient environment) under contemporary conditions or those of the past two centuries. Current practice is based on a human value‐judgement that views natural succession as the enemy. This view and the resulting actions to resist natural change are at variance with the more pervasive environmental management goal of maintaining natural systems by resisting human intervention. Such an approach reduces dune resilience to global climate change. We advocate an approach that views dunes as combined geomorphological and ecological systems capable of change in response to changing environmental drivers. Abstract : Modern management of coastal dunes can be described as "dune gardening." This approach is based on the maximisation of biodiversity and resists natural change. We advocate an alternative approach that views dunes as part of a dynamic coastal system and permits them to evolve and change.